2021
DOI: 10.1002/pmh.1534
|View full text |Cite
|
Sign up to set email alerts
|

Screening for borderline personality pathology on college campuses

Abstract: Although borderline symptoms show a normative decline throughout adulthood, severe psychosocial impairment often remains. Identifying personality pathology in college‐age students may help prevent “adaptive failure” that can occur during the critical period of development from puberty through the late 20s and thus reduce impairment later in life. The aims of the current study were to estimate the prevalence of borderline personality disorder (BPD) in a diverse college sample, determine which symptoms confer th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…In terms of sex differences, a related survey among a large number of university students in China demonstrated a higher prevalence among females than males [ 57 ], and a recent publication among American students found sex differences between females and males [ 7 ]. Our findings showed that the prevalence of BPD symptoms among both sexes was equal, which was congruent with those from a related meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of sex differences, a related survey among a large number of university students in China demonstrated a higher prevalence among females than males [ 57 ], and a recent publication among American students found sex differences between females and males [ 7 ]. Our findings showed that the prevalence of BPD symptoms among both sexes was equal, which was congruent with those from a related meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The literature review demonstrated that the prevalence of BPD among university students ranged from 0.5 to 32.1% and varied from time to time, as well as from culture to culture [ 2 , 7 ]. In China, the prevalence of BPD among Chinese undergraduate students ranged between 0.67 and 17.7% [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, while the present study demonstrated that BPDS is related to the male sex, many studies have found no sex differences [ 75 , 76 ]. Some studies, however, have found a higher prevalence in the female sex [ 77 , 78 ]. In addition, the present study found that older age groups and more years of studying were related to BPDS, in contrast to some studies with younger age groups [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…The growing shift from categorial to dimensional models of personality disorders in research literature and current classificatory systems of psychiatric disorders (Zimmerman, Chelminski, Young, Dalrymple & Martinez, 2013 ) reflect the importance of attending to vulnerabilities even at a sub-threshold level of personality disorder (Kaess Fischer-Waldschmidt, Resch & Koenig, 2017 , Cano, Sumlin & Sharp, 2021 ). In the context of parenting, studies that have included mothers with a diagnosis of BPD as well as those with sub-threshold symptoms suggest the presence of several challenges.…”
Section: Introductionmentioning
confidence: 99%